Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.736464
|View full text |Cite
|
Sign up to set email alerts
|

International High-Risk Clones Among Extended-Spectrum β-Lactamase–Producing Escherichia coli in Dhaka, Bangladesh

Abstract: Background:Escherichia coli is a major extended-spectrum β-lactamase (ESBL)–producing organism responsible for the rapid spread of antimicrobial resistance (AMR) that has compromised our ability to treat infections. Baseline data on population structure, virulence, and resistance mechanisms in E. coli lineages from developing countries such as Bangladesh are lacking.Methods: Whole-genome sequencing was performed for 46 ESBL–E. coli isolates cultured from patient samples at the International Centre for Diarrhoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…The normalized and pooled library was subjected to 150-base paired-end reads sequencing using the Mid-output v2.5 sequencing kit. Sequencing was performed at the icddr,b Genome Center using the Nextseq500 platform ( Mazumder et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The normalized and pooled library was subjected to 150-base paired-end reads sequencing using the Mid-output v2.5 sequencing kit. Sequencing was performed at the icddr,b Genome Center using the Nextseq500 platform ( Mazumder et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The predominant sequence types detected in this study were epidemiologically significant high-risk clones, including ST131, ST1193, ST12, ST73 and ST167. Our group previously reported these clones from Bangladesh amongst ESBL-producing lactose fermenting E. coli ( Mazumder et al, 2021 ). None of the studies has reported them from NLF E. coli except for ST1193 ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
“…ST131 is the predominant lineage of extraintestinal pathogenic E. coli worldwide and frequently harbors the CTX-M-15 ESBL gene as observed in the present study. 8487 Although ESBL carriage is not an indicator of acute health issues, it is nevertheless the most significant risk factor for ESBL- E. coli bacteremia. 3 The high rates of carriage observed here and elsewhere 64 suggests Bangladeshi children are at increased risk of future AMR infections.…”
Section: Discussionmentioning
confidence: 99%
“…ST131 is the predominant lineage of extraintestinal pathogenic E. coli worldwide and frequently harbors the CTX-M-15 ESBL gene as observed in the present study. [84][85][86][87] Although ESBL carriage is not an indicator of acute health issues, it is nevertheless the most significant risk factor for ESBL-E.…”
Section: A Lack Of An Observed Impact Of Water Chlorination On Esbl-e...mentioning
confidence: 99%